12x-6x+5+4x=10x+-5

Simple and best practice solution for 12x-6x+5+4x=10x+-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-6x+5+4x=10x+-5 equation:



12x-6x+5+4x=10x+-5
We move all terms to the left:
12x-6x+5+4x-(10x+-5)=0
We add all the numbers together, and all the variables
12x-6x+4x-(10x-5)+5=0
We add all the numbers together, and all the variables
10x-(10x-5)+5=0
We get rid of parentheses
10x-10x+5+5=0
We add all the numbers together, and all the variables
10!=0
There is no solution for this equation

See similar equations:

| -3-k=1 | | 5y+20=75 | | 6-10k+9k=6(1-5k)+3(9k+4) | | -2-n=9 | | 2x+41+x+x-17=180 | | 4x-12+7=9x+3 | | 2x+2x+18+42=180 | | 4x+6=5x+5 | | a+11+17a=29 | | 21x^2-79x+21=0 | | 50+3x+2x-15=180 | | m3=10 | | 3(+1)=8x+1-5x+2 | | 9x=9x+59 | | c3=1/27 | | 14x-15x=-29 | | 9x=9x=59 | | 5f+1+57=52 | | 2x+2+3x-5=5x-5 | | -x/5+13=31 | | AxB=120 | | y3=1/125 | | AxB=1120 | | -3.8-10x=230.303 | | -1.9+x=27.8 | | -7x-3x+5x=60 | | 1.9+x=27.8 | | x+6=62 | | 1/3(c-6)=12 | | 0.2x+0.8(94)=90 | | X(x+7)(x-4)=60 | | 8x+14=2(8x+14) |

Equations solver categories